All-screen-printed Dopant Paste Interdigitated Back Contact Solar Cell. (August 2015) - Scardera, Giuseppe; Inns, Daniel; Wang, Gonghou; Dugan, Shannon; Dee, Jeffrey; Dang, Thomas; Bendimerad, Karim; Lemmi, Francesco; Antoniadis, Homer
Abstract: We report results on the development of a cost-effective all-screen-printed interdigitated back contact (IBC) solar cell process. The rear side interdigitated doping pattern is achieved using screen printed n-type and p-type dopant pastes, and thermal drive-in. Our process provides excellent spatial definition of the doping pattern necessary for fabrication of an IBC solar cell. The doping approach used in this work overcomes limitations associated with conventional pastes, notably poor lateral doping control and reduced bulk lifetime. We demonstrate that wafer lifetime remains high, well above 1.5 msec, at the end of the solar cell process, enabling high cell efficiencies. Contacts are also achieved using screen printed fire-through metal pastes. We present pilot line data for n-type CZ silicon, 156 mm pseudo-square cells achieving just over 21% efficiency.